O Conceito De Trabalho Em Marcuse: Interpretação Do Artigo Sobre Os Fundamentos Filosóficos Do Conceito De Trabalho Da Ciência Econômica - Ramponi, Gabriel [UNIFESP] (2017)
The dissertation seeks to explore the theoretical sources for the development of the concept of Labor in Herbert Marcuse's work. Specifically, the focus is on the first period of the philosopher's work, with the article On the philosophical concept of Labor being the center of the research. There, Marcuse goes to Hegel and Marx to fundament the concept of Labor, counterposed to the posed by economic science. So, one chapter discuss Marcuse's Hegel, as Feenberg puts it, author by which we based ourselves to develop the influences on the interpretation that does Marcuse on Hegel. In a second moment, the discussion goes through the marcusean marxism that, according to Douglas Kellner, is caracterized by its heterodoxy. That is due, in great measure, by the discovery and publication of Marx's Economic-philosophical Manuscripts, text which Marcuse grants major relevance, specially to our problematic. The dissertation's final chapter, then, is exactly that that presents the article quoted before. Hopefully the previous closer discussion on the authors that will serv as Marcuse's foundations enriches the interpretation and reflection about the concept of Labor, as well as its relation with the economic science.